Compliance and Knowledge about Prescribed Medication among Elderly Home-care Recipients by Method of Providing Medications - Yanagi, Hisako; Tomura, Shigeo; Okuno, Junko (Nihon Rōnen Igakkai zasshi, 2001)
After long-term care insurance commenced in April 2000, various types of in-home care began, including delivery of prescriptions medicines to the elderly. However, the effects of in-home care workers on patient drug compliance are unclear as yet. In this study, we examined the characteristics of the care workers who delivered prescription medicines to the elderly, and analyzed the effects on patient drug compliance and knowledge about medication. The subjects included 163 homecare recipients aged 60 and older, who were taking more than one prescribed drug, who ranked worse than J-2 who were physically disabled, and cognitively normal. The rate of good compliance was 71.1% when pharmacists provided the prescribed drugs and counseled the patients at home, which rate was significantly higher than that of self supply by the patient (35.0%), caregiver supply (44.7%), and home-helper supply (0.0%). The difference in compliance may be explained by the possibility that when caregivers and home-helpers provided prescribed medications, thorough and accurate information about the drugs were not clearly imparted to the elderly, whereas when pharmacists provided prescribed medications, a pharmacological examination was performed and thorough and accurate information was communicated to the elderly. In the group counseled by pharmacists, knowledge about the effects and purpose of medication positively correlated with drug compliance. However, in the group provided drugs by caregivers, knowledge about the effects and purpose of medication inversely correlated with drug compliance. These findings suggested that the elderly in the latter group chose, to some degree, not to comply. Many elderly people had difficulty getting to hospital, and 23.1% of the patients in this study had not consulted the doctor for more than 2 months. Our data suggest that drugs provided by pharmacists and the availability of pharmacist counseling play an important role in preventing drug noncompliance and in making home care more effective, and also suggest that it is important for pharmacists to cooperate with other care workers, including a care-manager, and to provide written information on prescription medicine to caregivers and home-helpers as well as to elderly patients.